Moderate Islamic Education: Responding To The Concepts of Pluralism And Tolerance Within The Framework of Rahmatan Lil-Alamin - sanusi, Aan (RAHMATAN LIL ALAMIN: Journal of Peace Education and Islamic Studies, 2024)
This discussion aims to delve deeper into the concepts of pluralism and tolerance within the framework of "rahmatan lil alamin" (blessings for all creation). The goal is to gain a clear understanding of the actual attitudes, levels, and limitations of tolerance. This research adopts a literature review approach, a type of study where data is sourced from literature related to the research object, and subsequently, the content is analyzed. From this study, it is emphasized that the concepts of pluralism and tolerance within the framework of "rahmatan lil alamin" reflect an inclusive perspective and a commitment to peace as espoused in Islamic teachings. The concept of "rahmatan lil alamin" teaches Muslims to extend mercy and compassion to the entire universe, including the relationships between believers and non-Muslims. Within this framework, pluralism and tolerance become key principles for fostering harmony in diverse societies. Fundamentally, pluralism is a result of moral tolerance and passive coexistence. Moral tolerance appreciates surface-level differences, while passive coexistence acknowledges the existence of others without actively preventing conflicts.